Contextualization of Distance Learning Perspective of Tarbawi Hadith - Iffatut Tazkiyyah; Faqih Abdul Aziz; Aisyah Rochmah Nuraini; Dzatan Nitoqoin; Azmi Izuddin (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
The development of digital technology encourages the implementation of Distance Learning (PJJ), but the practice still faces pedagogical and ethical challenges and is often understood as a purely modern phenomenon. In fact, the Islamic scientific tradition has recognized the transmission of knowledge through intermediary media, as reflected in the hadith about the scientific interaction between Marwān bin al-Ḥakam and Zayd bin Thābit. This research aims to analyze the relevance of the tarbawi hadith in building the conceptual framework of PJJ in the digital era. The research uses a literature study method with a qualitative-descriptive approach. Primary data is sourced from Al-Muwaṭṭa' by Imam Mālik and Islamic educational literature, while secondary data is obtained from contemporary digital learning studies. The analysis was carried out through content analysis to identify tarbawi values that are relevant to the characteristics of PJJ. The results of the study show that the hadith contains the principles of scientific trust, information verification, communication manners, message documentation, and flexibility of learning methods. These findings confirm that PJJ has historical roots in Islamic traditions and can be developed as an effective, ethical, and spiritually valuable digital learning model.